PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI - Septi Irmalia (CV. Amerta Media, 2020)
The child is a boon and mandate entrusted by God to His servant who will be asked for the responsibility in the Hereafter. The obligation as a parent is to provide education to children starting from an early age. The development of early childhood is strongly bound by the environment and the family. This paper aims to describe the role of parents to the education of children. The study in this paper uses literature study or library research method. The result of this study is that family is the first place where children get education. Children's character and personality is formed first in the family. Parents should have a concept or provision in educating their children that includes moral or character education, science education, religious education, be fair to the children, and give attention and affection to children. Parents become role models for their children. Therefore, the role of parents is very important in the development and formation of children's character from an early age.Key Words: Parents, Charater education, Chilhood Education, family environment